Digitalisation, institutions and governance, and diffusion : mechanisms and evidence - Labhard, Vincent; Lehtimäki, Jonne; Baccianti, Claudio (Taylor & Francis, 2025)
Digitalisation can be described as a sequence of technology and supply shocks which affect the economy through employment and labour markets, productivity and output, and competition and market structure. This paper focuses on how digitalisation - the process of diffusion of digital technologies - is affected by institutions and governance. It discusses a number of theoretical mechanisms and empirical evidence for different sets of European and other countries while also accounting for cross-section dependence that might be caused by technology spillovers. The results indicate that a higher quality of institutions is usually associated with both a greater speed of diffusion and a greater spread of digital technologies. Additionally, some negative effects from high levels of governance are observed. The results also suggest that there are large, policy-relevant differences in the diffusion process depending on the technology, the level of development as well as the state of technological change of a country.